The influence of γ-fibre texture on the grain boundary character distribution of an IF-steel. (1st January 2023) - Beladi, Hossein; Tari, Vahid; Rollett, Anthony D.; Rohrer, Gregory S.
Abstract: The current study revealed that the development of γ-fibre texture in IF-steel through static recrystallisation alters the distribution of grain boundary misorientations and plane orientations. In the initial transformed condition, the grain boundary plane distribution has a maximum at the (110) orientation. However, as the intensity of the γ-fibre texture increased, the maximum shifted to (111) and intensified. Furthermore, the presence of γ-fibre texture gradually increased the low angle boundary population at the expense of high angle boundaries, leading to a nearly uniform misorientation angle distribution. A calculation of the disorientation distribution assuming random orientations along the γ-fibre showed a flat distribution in the domain from 0 to 60°, consistent with the observations. The presence of γ-fibre texture changed the intensity, but not the shape of the grain boundary distribution at ∑3 = 60°/[111], which displayed maxima at low energy {112} symmetric tilt boundaries. Graphical abstract: Image, graphical abstract